2012
DOI: 10.1366/11-06396
|View full text |Cite
|
Sign up to set email alerts
|

An On-Line Near-Infrared (NIR) Transmission Method for Determining Depth Profiles of Fatty Acid Composition and Iodine Value in Porcine Adipose Fat Tissue

Abstract: The present work describes a measurement method using spatially resolved near-infrared (NIR) spectroscopy to determine porcine carcass fat quality as a function of the distance to the skin by estimating its iodine value (IV). The new method is capable of performing on-line carcass grading at full production speed (approximately 1000 carcasses per hour). The method is demonstrated in an experiment where 35 carcasses were sampled at an abattoir, selected from three feeding groups. The NIR transmission instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Hence, this sort of representation shows the degree of convergence of the various models computed for each variable. It can be observed that, for all the modeled chemical variables, the most frequently selected region is the one corresponding to the spectral bands centered at 5785 and 5670 cm −1 , in which the absorption bands related to the C-H stretching first overtone of CH 2 and CH 3 groups are located (Sørensen et al 2012;González-Martin et al 2005;Pérez-Juan et al 2010;Li et al 1999).…”
Section: Variable Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, this sort of representation shows the degree of convergence of the various models computed for each variable. It can be observed that, for all the modeled chemical variables, the most frequently selected region is the one corresponding to the spectral bands centered at 5785 and 5670 cm −1 , in which the absorption bands related to the C-H stretching first overtone of CH 2 and CH 3 groups are located (Sørensen et al 2012;González-Martin et al 2005;Pérez-Juan et al 2010;Li et al 1999).…”
Section: Variable Selectionmentioning
confidence: 99%
“…Finally, in the work by Li et al (1999) the bands near 8475 and 4675 cm −1 are attributed to strong -CH=CH-(cis double bond) overtone and combination band vibrations, respectively. Interestingly, most of the bands selected for calibrating IV were the same selected by iPLS in the work by Sørensen et al (2012).…”
Section: Variable Selectionmentioning
confidence: 99%
See 3 more Smart Citations